Geological and Industrial Characterization of the Mylonite Belonging to the Granja Complex, Morrinhos - CE - Veras Diógenes, Davi Henrick; Clezar Mattos, Irani (Anuário do Instituto de Geociências, 2025)
Considering that establishing an ornamental stone deposit requires various preliminary studies, this research aimed to identify the potential of a mylonite belonging to the Granja Metamorphic Complex in the Médio Coreaú Domain. To this end, geological mapping, technological characterization, and reuse studies were conducted. The technological characterization considered both national standards, developed by ABNT, and European and American standards. For determining the reuse options for the cutting and dismantling waste of the material, tests were conducted for its use as a partial replacement for coarse aggregate in concrete, as eco-filler, and for the production of artificial agglomerated stone. In the end, in addition to understanding the geological history of the rock, it was possible to determine its safe use as an ornamental stone and the best ways to utilize the waste.